SUBSTANTIATION OF POSSIBILITY TO USE WASTE OF SEA CUCUMBER PROCESSING FOR PRODUCTION OF SOFT DRINKS - E. V. Okhota; A. I. Chepkasova; E. P. Karaulova; T. N. Slutskaya (Известия ТИНРО)
The broth of sea cucumber was decolorized with mineral sorbents, as perlite and bentonite, and with chitosans of crab carapace and shrimp shell. The chitosans were the most effective in sorption and subsequent removal of the protein-pigment complex, providing the decolorization degree of 35–55 %. Besides, the content of glycosides in the broth was twice decreased. The amino sugars content changed in dependence on the chitosan origin: the chitosan of crab carapace did not influence on this parameter, but the chitosan of shrimp shell caused its halving. For the optimal combination of chemical compounds in the broth, the chitosan with high molecular weight (1300 kDa) extracted from crab carapace should be used for decolorizing. Preliminary fermentation of the broth with Protamex increased concentration of biologically active peptides with low molecular weight in the solution. The fermented and decolorized broth of sea cucumber has good organoleptic properties and high content of biologically active components, as glycosides, amino sugars and low molecular weight peptides, so could be used as the basis for nonalcoholic tonic drinks.